2017
DOI: 10.1055/s-0037-1606243
|View full text |Cite
|
Sign up to set email alerts
|

Applying the Newman-Peacock Prognostic System to a Portuguese Obstetrical Population - A Useful Tool?

Abstract: The Newman-Peacock score had a poorer performance among our population compared to its performance in the original study, but the results suggest that this score is still a useful tool to guide our clinical practice and counsel the candidate regarding ECV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Of the 17 new articles, 4 had some form of overlap with articles from the prior systematic review (Figure 2). Two 25,26 were external validation studies of a 1993 prediction model 27 in a new population by a new investigational team; one of the validation studies also described a new model 26 . A third article 28 had a partially overlapping dataset with the investigational team's prior articles 22,23 , but proposed a model for predicting delivery type, while the prior articles focused on predicting cephalic presentation immediately after ECV.…”
Section: Relationships Between Articlesmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 17 new articles, 4 had some form of overlap with articles from the prior systematic review (Figure 2). Two 25,26 were external validation studies of a 1993 prediction model 27 in a new population by a new investigational team; one of the validation studies also described a new model 26 . A third article 28 had a partially overlapping dataset with the investigational team's prior articles 22,23 , but proposed a model for predicting delivery type, while the prior articles focused on predicting cephalic presentation immediately after ECV.…”
Section: Relationships Between Articlesmentioning
confidence: 99%
“…The results of the study quality assessment based on the signaling questions are shown in Table 4. Out of 17 new articles, 10 studies were identi ed as having low overall risk of bias and high study quality 22,[29][30][31][32]35,37,[40][41][42] , 6 studies were identi ed as having moderate bias and moderate study quality 25,33,34,38,39,43 , and 1 was considered to have high bias and low quality 26 . This is in addition to Velzel et al's assessment of the 8 prior articles of which 4 were low risk of bias and high study quality and 4 were moderate risk of bias and study quality 10 .…”
Section: Quality and Biasmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 17 new articles, 4 had some form of overlap with articles from the prior systematic review (Figure 2). Two 29,30 were external validation studies of a 1993 prediction model 31 in a new population by a new investigational team; one of the validation studies also described a new model 30 . A third article 32 had a partially overlapping dataset with the investigational team's prior articles 22,23 , but proposed a model for predicting delivery type, while the prior articles focused on predicting cephalic presentation immediately after ECV.…”
Section: Relationships Between Articlesmentioning
confidence: 99%